Neurophysiological evaluation of short-term outcome of pharmacological treatment of diabetic neuropathy - Cvijanović, Milan; Simić, Svetlana; Kopitović, Aleksandar; Raičević, Ranko (Vojnosanitetski pregled, 2017)
Background/Aim. Diabetic polyneuropathy (DPN) is a very frequent and progressive disease that severely impairs the overall quality of life, accompanied by a high rate of disability. For these reasons, the testing of therapeutic agents for this disease is increasing. Methods. We tested the most frequently used drugs for diabetic neuropathy in our area, along with electrophysiological monitoring in order to avoid subjectivity and the "placebo effect". A total of 120 patients were divided into four groups: three groups who received alpha-lipoic acid, benfotiamine or gabapentin respectively, and the control group who did not receive any treatment. In all the patients we analyzed motor conduction velocity, distal latency, sensory conduction velocity, F wave and F wave chronodispersion before and after treatment with each drug. Results. It is evident that some drugs had a favorable impact on the condition of the peripheral nerves. Alpha-lipoic acid and benfotiamine had an impact on the recovery of the nerve, i.e. pathophysiological processes, whereas gabapentin had no impact on the recovery, similarly to the control group without any treatment. Electrophysiological indicators had different sensitivity to detect conditions of the peripheral neurons. The best effect, in terms of increased sensory conduction velocity, had the patients treated with alpha-lipoic acid. Conclusion. The effect of alpha-lipoic acid and benfotiamine on the condition of peripheral nerve was evident. The failure of recovery, i.e. deterioration of electrophysiological parameters in patients who did not receive neuroprotective therapy suggests the need of permanent medication and periodic electrophysiological monitoring of patients with diabetic polyneuropathy.
Keywords: diabetic neuropathies; electromyography; drug therapy; thioctic acid; thiamine monophosphate; gabapentin; treatment outcome